O cluster da construção em Minas Gerais e as práticas decolaboração e de gestão do conhecimento: um estudo das empresas daRegião Metropolitana de Belo Horizonte (MG) - Antonio Braz de Oliveira e Silva (2007)
The process of sharing information inside firms plays a fundamental role to enhance knowledge. Innovation is a consequence of this sharing, as the result of the effort of solving problems which arise from changes in business environment. Its consequence is the introduction of new procedures, routines, devices and expertise among employees. The creation of knowledge networks inside firms performs the so called social capital, which is part of their intellectual capital. Firms dont operateisolated in the market, theres also a tendency to create networks. Organizational knowledge networks among firms inside a cluster are relevant to create and process innovation. The construction industry presents a very special characteristic, as firms inside this industry are organized to create unique products: every single project has its own characteristics. Firms in this industry organize their production involving other construction firms, by subcontracting others to perform a unique project. Although subcontracting networks has been a practice in this industry long before other ones, less was studied about it. Also rare are studies about their organization in clusters. An input-output model was drawn to evidence the construction industry cluster in the State of Minas Gerais in Brazil. This model was complemented by social network analysis and by documental research. A survey was conducted to analyze the process of information sharing inside firms of the construction industry and to enlighten the relevance of social capital and relational networks. Results support the existence of such a cluster. Firms inside this cluster have been introducing innovation based on information technology. Although organizational knowledge networks are not yet their main concern, this kind of innovation enhances their human and socialcapital.